A THE MANAGEMENT OF WATER RESOURCES АROUND THE WORLD: A REVIEW - Fidani, Drenushe; Hodza, Yasemin (International Scientific Journal Vision, 2021)
Water resources are unevenly distributed in time and space. They must be managed in order to control the presence of water on Earth. This is what this paper deals with. The paper gives a review of management of water resources in some countries, namely: Turkey, Japan, Netherlands, India, Italy and China. It is concluded that different countries use different methods and technics to manage water resources. Some of them are still useful, although are quite old, but there are also modern methods. Large cities are particularly vulnerable to flooding due to their huge concrete structures with a lack of green areas to absorb rain. As a result, floods remain a central sore point for most of them